A qualitative study of food sociality in three provinces of South China: social functions of food and dietary behavior - Yan, Youxuan; Petersen, Jindong Ding; Lin, Liuting; Chen, Juncai; Li, Xiyi; Ji, Guiyuan; Zhang, Fan (Frontiers in Nutrition, 2023)
Background: Food sociality refers to the exploration of food production, exchange, distribution, and consumption and influences on cultural communication and social meaning. This study aimed to investigate food sociality in three provinces of South China to provide theoretical and practical evidence of food sociality in the region and to revise nutrition policies. Materials and methods: We conducted a qualitative study comprising 25 experts in the fields of nutrition, sociology, food science, and agriculture from Hainan, Guangdong, and Guangxi Province by using a semi-structured in-depth interview, which included pre-determined 28 questions from six aspects. The interviews were conducted between November 2020 and March 2021. Verbatim transcripts were analyzed thematically using NVivo 11.0. Results: Of the 25 experts, the mean age was 50.6 (SD=8.4) years, 15 (60%) were male, and 22 (88%) with a master degree or above. The analysis showed that food sociality in three provinces of South China mainly comprises social functions of food and dietary behavior. Regarding social functions of food, the experts expressed that food is symbols of local culture (72%, 18 experts), presents social status and economic power (40%, 10 experts), and is special occasion of traditional customs and etiquette activities (60%, 15 experts). In terms of social functions of dietary behaviors, the majority of experts indicated that food is social communication tool (72% experts), has its geographical characteristics (80% experts), and to some extent, used as a proxy for reward or punishment. Furthermore, festival is one of the core elements of food sociality in the region, although food safety is a major concern. Some of dietary behaviors such as abundance of afternoon tea and persuading drinking may increase risk for chronic diseases. Conclusion: Food sociality in three provinces of South China mainly comprises social function of food and dietary behavior. It is a combination of local culture, social status and economic power, traditional customs, rewards and punishments, geographical food preference, and social communication tools. The authors recommend increasing food safety at festivals and to promote healthy eating behaviors in order to improve overall population health in this region.